Complexos derivados do ácido valproico - teratogenicidade embrionária e atividade anticonvulsivante em Zebrafish (Danio rerio) - Grünspan, Lauren Dockhorn (My University, 2016)
The most important determinant of quality of life in patients with epilepsy is complete seizure control, and therefore this should be the ultimate goal of pharmacological therapy. Unfortunately, around 30% of epileptic patients still suffer with refractory epilepsy. Metal ions have been frequently incorporated into pharmaceuticals for therapeutic or diagnostic purposes and the research. In this study, we access the embryo toxicity and anticonvulsant activity of 4 novel metallodrugs, with Zn+2 and Cu+2, derivative with valproic acid and the N-donor ligand in adult zebrafish pentylenetetrazole epileptic seizure model. [Cu(Valp)2Bipy] LC50 in 48 Hours Post Fertilization (hpf) was 0.22 μM and 0.12 μM in 96 hpf followed by [Zn(Valp)2Bipy] (LC50 = 10 μM). This same metallodrugs ([CuValp)2Bipi] 10 mM/Kg and [Zn(Valp)2Bipi] 30 mM and 100 mM/Kg) displayed a superior activity reducing the seizure intensity compared to Sodium Valproate (175 mM/Kg). As conclusion, among all, the [Cu(Valp)2Bipi] showed the best anticonvulsant effects, but due to its toxic effects on embryos and larvae, the [Zn(Valp)2Bipi] should be considered the most promising for future studies as anticonvulsant drug.
A epilepsia é uma patologia que afeta 50 milhões de pessoas, sendo que cerca de 30% dos pacientes apresentam epilepsia refratária, ou seja, não respondem a terapia medicamentosa disponível. Portanto, é necessária a busca contínua de novos fármacos. Os complexos organometálicos vêm ao encontro a esta necessidade conjugando moléculas já aplicadas na terapia (como o ácido valproico), a metais essenciais e outros ligantes a fim de aprimorar os efeitos farmacológicos. Neste trabalho foram testados quatro complexos derivados do ácido valproico: [Cu(Valp)2Fen] , [Cu(Valp)2Bipi], [Zn(Valp)2Fen] e [Zn(Valp)2Bipi], através do screening toxicológico embrionário e atividade anticonvulsivante em zebrafish induzidos por pentilenotetrazol (PTZ). O complexo [Cu(Valp)2Bipi] apresentou maior toxicidade embrionária (CL50=0.12 μM), seguido pelo [Zn(Valp)2Bipi] (CL50 = 10μM). Estes mesmo complexos nas doses de 10 mM/Kg, 30 mM/Kg e 100 mM/Kg para derivado contendo zinco a intensidade das convulsões em relação ao valproato de sódio (175 mM/Kg) em peixes adultos, demonstrando ação superior ao fármaco tradicional. Devido a baixa toxicidade aliada a ação anticonvulsivante evidente selecionamos o derivado [Zn(Valp)2Bipi] para estudos futuros em modelos complexos de epilepsia.
Keywords: Ácido valproico; Epilepsia - Tratamento; Princípio ativo (Farmacologia); Toxicologia; Farmacologia; Valproic acid; Epilepsy - Treatment; Active ingredient (Pharmacology); Toxicology; Pharmacology